Ngurra - kurlu - Egan Nungarrayi, Jeannie (Yuendumu, [N.T.] : Warlpiri Literature Production Centre, 1980)
Primer.
Text in Warlpiri with English translation.
Keywords: Warlpiri language -- Readers; Warlpiri language (C15) (NT SF52-04); Education - Language - Indigenous languages - Readers and primers; South Central Northern Territory (NT)